2019
DOI: 10.34172/jsums.2019.24
|View full text |Cite
|
Sign up to set email alerts
|

Wives’ perception of sexual relationship with narcissistic men: Results of a qualitative thematic analysis with Iranian women

Abstract: Background and aims: Many studies have investigated the interpersonal dimensions of narcissism, though women’s perceptions of sexual relationship with a narcissistic individual have rarely been the topic of interest. The main purpose of this study was to investigate the sexual lived experiences of women living with narcissistic men. Methods: To this end, a qualitative thematic analysis was used to have a better understanding of the concept. A total of 31 women were selected through convenience sampling techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Research has suggested the link between narcissism and the problematic use (and loss) of others' money (Jones, 2013). Further findings have highlighted the link between narcissism, sexual coercion, infidelity and sexual aggression within romantic relationships (Altinok & Kilic, 2020; Lamarche & Seery, 2019; Moradi et al, 2019). However, while the majority of research has focused on male narcissistic samples, research has also demonstrated the presence of sexual aggression, coercion and intimate partner violence in females with pathological narcissism (Blinkhorn et al, 2015; Green et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested the link between narcissism and the problematic use (and loss) of others' money (Jones, 2013). Further findings have highlighted the link between narcissism, sexual coercion, infidelity and sexual aggression within romantic relationships (Altinok & Kilic, 2020; Lamarche & Seery, 2019; Moradi et al, 2019). However, while the majority of research has focused on male narcissistic samples, research has also demonstrated the presence of sexual aggression, coercion and intimate partner violence in females with pathological narcissism (Blinkhorn et al, 2015; Green et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Marital conflicts play significantly mediating roles in the relationships of difficulties in emotion regulation with relationship quality and sexual satisfaction (15). Sexual satisfaction refers to satisfaction (satisfaction with sex), communication (verbal communication and dialogue with spouse such as the easy expression of feelings and feedback on sex) (16), adjustment (couples' awareness of their spouses' sexual needs and efforts for adjustment to spouse in sex), sexual anxiety (women's anxiety about their husbands due to sexual problems and their spouses' sexual relationships with others) (17,18), and personal anxiety (the anxiety about sexual problems and their effects on other aspects of women's life that can prevent their pleasure and peace of mind in their personal life) (19). Since the Iranian society is now in a transition state with traditional rituals, most couples live in traditional families and prefer putting up with very low-quality married lives to experiencing the stress of divorce.…”
Section: Introductionmentioning
confidence: 99%